2010
DOI: 10.1021/jf100899u
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Properties of Lactoferricin B-Derived Peptides

Abstract: A set of eight lactoferricin B (LfcinB)-derived peptides was examined for inhibitory effects on angiotensin I-converting enzyme (ACE) activity and ACE-dependent vasoconstriction, and their hypotensive effect in spontaneously hypertensive rats (SHR). Peptides were derived from different elongations both at the C-terminal and N-terminal ends of the representative peptide LfcinB(20-25), which is known as the LfcinB antimicrobial core. All of the eight LfcinB-derived peptides showed in vitro inhibitory effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Tail systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured by the noninvasive tailcuff method 19 with computer-assisted BP-2010 Series tail measurement equipment (Softron Beijing Biotechnology Co., Ltd). 11003800004211, Beijing HFK Bioscience Co., China).…”
Section: Stabilities Against Simulated Gastrointestinal Digestion On mentioning
confidence: 99%
“…Tail systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured by the noninvasive tailcuff method 19 with computer-assisted BP-2010 Series tail measurement equipment (Softron Beijing Biotechnology Co., Ltd). 11003800004211, Beijing HFK Bioscience Co., China).…”
Section: Stabilities Against Simulated Gastrointestinal Digestion On mentioning
confidence: 99%
“…Recently, some studies have demonstrated antihypertensive effects of this food-derived peptide and its hydrolysate in normal and spontaneously hypertensive rats (SHR) [17, 18]. The NO-dependent vasodilation, inhibition of angiotensin I-converting enzyme (ACE) activity, and inhibition of endothelin-converting enzyme (ECE) activity have been suggested as the mechanisms responsible for antihypertensive effects of LF [1921].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the in vitro ACEinhibitory activity showed by LfcinB-derived peptides, in the in vivo experiments only LfcinB20-25, with the higher IC50 value of all of them, showed a moderate antihypertensive effect (-16.7 ± 3.2 mm Hg) in SHR, that was 7.7 % reduction from baseline SBP. 81 Peptides derived from other LF regions showed similar behavior on in vivo assays (from -13.2 mm Hg to -26.8 mm Hg) than that expected from in vitro potencies (from 0.35 µM to 105.3 µM). Although the IC50 values of LF-derived peptides were by far higher than that of ACE-inhibitory drug captopril (0.022 µM), 89 in the conditions tested, oral administration of DPYKLRP, LRP and LIWKL resulted in a significant decrease in SBP (13.4% reduction from baseline for DPYKLRP and LRP; 12.1% reduction for LIWKL) similar to that of captopril (14% reduction).…”
Section: Ace Inhibitionmentioning
confidence: 71%
“…81 Also, RPYL and LIWKL showed similar inhibitory effects on ACE-dependent vasoconstriction (14% and 22% response reduction over the control conditions, respectively) despite their 100-fold different in vitro potencies (IC50 values of 56.5 and 0.47 µM, respectively). Although this discrepancy deserves further research, a methodological detail could at least in part account for it, since in vitro tests were carried out with porcine ACE, while rabbit arteries were used in ex vivo tests, and variations in the inhibition profiles of ACE from different species have been reported.…”
Section: Ace Inhibitionmentioning
confidence: 79%
See 1 more Smart Citation